2018
DOI: 10.1136/bmjsem-2017-000316
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short and long moderate-intensity exercises in modifying cardiometabolic markers in sedentary Kenyans aged 50 years and above

Abstract: ObjectivesWe compared effects of shorter moderate-intensity exercise time (<10 min bouts) on cardiometabolic parameters with the current recommendations among elderly adults.MethodsFifty-three sedentary individuals aged ≥50 years were divided into exercise groups1: male and2 female short-duration bouts (MS and FS, respectively), and3 male and4 female long-duration bouts (ML and FL, respectively). Short-duration bouts consisted three 5–10 min moderate-intensity jogging sessions daily, and long-duration bouts co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Among the males from the two interventional groups, adherence rates were similar while females on shorter bouts of exercise had a 5-percentage-points higher adherence compared to those in the longer bouts' group. Previous work on similar exercise regimes from the same setting have equally shown higher adherence in both males and females performing shorter bouts in an older population, suggesting that such regimes may be more appealing [30]. The current study equally suggests that across all adult ages, adoption of shorter exercise bouts may improve exercise adherence since individuals maintaining their exercise prescriptions matched those performing the WHO standard exercise regimes.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Among the males from the two interventional groups, adherence rates were similar while females on shorter bouts of exercise had a 5-percentage-points higher adherence compared to those in the longer bouts' group. Previous work on similar exercise regimes from the same setting have equally shown higher adherence in both males and females performing shorter bouts in an older population, suggesting that such regimes may be more appealing [30]. The current study equally suggests that across all adult ages, adoption of shorter exercise bouts may improve exercise adherence since individuals maintaining their exercise prescriptions matched those performing the WHO standard exercise regimes.…”
Section: Discussionsupporting
confidence: 56%
“…The search for a feasible way to prevent transition of prehypertension to hypertension therefore is necessary. We recently found that moderate-intensity exercise regimes involving bouts of <10 minutes but whose cumulative weekly time equals current World Health Organization (WHO) recommendations of 150 minutes has higher appeal and, yet, confer appreciable health benefits on sedentary normotensive individuals aged �50 years [30][31][32]. Existing guidelines of moderate intensity exercise for adults have traditionally been achieved by performing 30-60 minute bouts of exercise for 3-5 days weekly, and, for hypertension, there is advocacy to do this daily [27,32,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opinions differ on the benefits of short exercise bouts,11–17 and a different approach in regime, population or setting that addresses the lack of PA/exercise could be useful. In a previous study involving the same population as in this study, we found that shorter exercise sessions are beneficial in improving cardiometabolic markers and body composition 18 19. However, the few studies that have tested the effect of supervised exercise bouts on cardiac performance among the elderly have shown conflicting results 20–22.…”
Section: Introductionmentioning
confidence: 49%
“…Mostly spinal postural defects can prevent respiratory function. [11,12] Flexicurve using flexi ruler is the reliable method to assess spine postural defects. Cervical lordosis index, kyphosis index and lumbar index is used to measure defects at cervical, thorasic and lumbar spine respectively.…”
Section: Posture Correctionmentioning
confidence: 99%